THE EFFECT OF ORGANIZATIONAL COMMUNICATION, ENVIRONMENT, AND WORK CULTURE ON WORK MOTIVATION ON CIVIL SERVANTS IN BLORA REGENCY - Kasidin Kasidin; Rasno Rasno (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research purposes were determined the effect of organizational communication, environment and work culture on employee work motivation of Civil Servants in Blora Regency. The research type is quantitative research and hypotheses testing. The population is Civil Servants in Blora Regency. The sampling technique used slovin sampling technique. The sample is 80 respondents. To obtain data, the researchers used the questionnaires which was distributed to civil servants in Blora Regency. Based on the results of the t test, it can be concluded that: 1) the t value of the organizational communication variable (X1) is 5.849 > t table 0.2213 with a significant value of 0.000 t table 0.2213 with a significant value of 0.000 t table 0.2213 with a significant value of 0.000